Correction to: Depressive symptoms in individuals with family members requiring ADL assistance - Junhyun Kwon; Eun-Cheol Park; Woorim Kim; Dong-Woo Choi; Sung-In Jang (Komiyama Printing Co. Ltd, 2019)
Following publication of the original article [1], the authors reported an error in Table 2 in their paper. The table entry "Men's P value" was mistakenly included under the table heading "Women". The original article [1] has been updated.